2021
DOI: 10.1155/2021/8367802
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Sprouts Extracts Is Correlated with Their Anti-Obesity and Anti-Inflammatory Effects in High-Fat Diet-Fed Mice

Abstract: Obesity is closely associated with oxidative stress and chronic inflammation leading to related metabolic diseases. Some natural extracts or polyphenols reportedly possess anti-obesity and anti-inflammatory effects as well as antioxidant activity. In this study, we assessed the correlations between the antioxidant, anti-obesity, and anti-inflammatory activities of plant extracts with potent antioxidant activity in diet-induced obese mice. Sprouts of Cedrela sinensis (CS) and Oenothera biennis L. (OB) were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…In this study, chronic stress exposure increased the inflammatory response and cellular cytotoxicity in brain tissue; however, EFCS downregulated the inflammatory expression levels of caspase-1, TNF-α, IL-1β, p-JNK, Bax, and p-tau in brain tissues ( Figure 8 and Figure 9 ). Similar to these studies, sprouts of Cedrela sinensis suppressed the levels of cytokines such as IL-6 and TNF-α and increased antioxidative enzymes such as glutathione peroxidase (GPx), glutathione S-transferase (GST), and SOD levels [ 86 ]. Rutin contained in Cedrela sinensis significantly decreased p-JNK, Bax, and caspase-3 levels in CdCl 2 -treated rat brain [ 87 ].…”
Section: Discussionmentioning
confidence: 87%
“…In this study, chronic stress exposure increased the inflammatory response and cellular cytotoxicity in brain tissue; however, EFCS downregulated the inflammatory expression levels of caspase-1, TNF-α, IL-1β, p-JNK, Bax, and p-tau in brain tissues ( Figure 8 and Figure 9 ). Similar to these studies, sprouts of Cedrela sinensis suppressed the levels of cytokines such as IL-6 and TNF-α and increased antioxidative enzymes such as glutathione peroxidase (GPx), glutathione S-transferase (GST), and SOD levels [ 86 ]. Rutin contained in Cedrela sinensis significantly decreased p-JNK, Bax, and caspase-3 levels in CdCl 2 -treated rat brain [ 87 ].…”
Section: Discussionmentioning
confidence: 87%
“…It has been also reported that Oenothera biennis (evening primrose) induced a small but significant reactivation of senescent human dermal fibroblasts (19). It also showed antioxidative and anti-inflammatory actions in diet-induced obese mice (20). Likewise, Stevia rebaudiana extract rich in phenols and flavonoids possessed significant antioxidant activities and a promising whitening effect, having potential use as active ingredients in cosmetic products (21).…”
Section: Comparison Of Anti-uvc Activity Between Two Groups Of Herb E...mentioning
confidence: 95%
“…Stingless bee propolis exhibits antioxidant activity that can counteract, and repair cellular damage induced by free radicals [10]. These free radicals are constantly generated within human bodies during regular metabolic processes and can impair cellular function, potentially initiating the development of pathological conditions such as cardiovascular disease, cancer, and neurological disorders [11].…”
Section: Introductionmentioning
confidence: 99%